MENGEMBANGKAN MOTORIK HALUS ANAK MENEMPEL SESUAI POLA MENGGUNAKAN PJBL, EXPLICIT INSTRUCTON DAN MEDIA BAHAN ALAM - Marni, Marni; Purwanti, Ratna (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This study was motivated by the low level of children's fine motor skills in performing pattern-sticking activities in group B at Khadijah Plus Islamic Kindergarten, Banjarmasin. To overcome this problem, this study applied a combination of Project Based Learning (PjBL) learning models, Explicit Instruction, and the use of natural media as an effort to improve children's fine motor skills. The main objective of this study was to describe teacher and child activities during the learning process, and to analyze the results of children's fine motor development, especially in the skill of sticking according to the patterns taught. This study used a qualitative approach with the type of Classroom Action Research (CAR) which was carried out in four meetings. The results of the data analysis showed that teacher activity reached a percentage of 94% with the category of